KCNJ15 deficiency promotes drug resistance via affecting the function of lysosomes - Xinbo Qiao; Yixiao Zhang; Zhan Zhang; Nan Niu; Haonan Li; Lisha Sun; Qingtian Ma; Jiawen Bu; Jinchi Liu; Guanglei Chen; Jinqi Xue; Yongliang Yang; et al. (Elsevier, 2023)
The altered lysosomal function can induce drug redistribution which leads to drug resistance and poor prognosis for cancer patients. V-ATPase, an ATP-driven proton pump positioned at lysosomal surfaces, is responsible for maintaining the stability of lysosome. Herein, we reported that the potassium voltage-gated channel subfamily J member 15 (KCNJ15) protein, which may bind to V-ATPase, can regulate the function of lysosome. The deficiency of KCNJ15 protein in breast cancer cells led to drug aggregation as well as reduction of drug efficacy. The application of the V-ATPase inhibitor could inhibit the binding between KCNJ15 and V-ATPase, contributing to the amelioration of drug resistance. Clinical data analysis revealed that KCNJ15 deficiency was associated with higher histological grading, advanced stages, more metastases of lymph nodes, and shorter disease free survival of patients with breast cancer. KCNJ15 expression level is positively correlated with a high response rate after receiving neoadjuvant chemotherapy. Moreover, we revealed that the small molecule drug CMA/BAF can reverse drug resistance by disrupting the interaction between KCNJ15 and lysosomes. In conclusion, KCNJ15 could be identified as an underlying indicator for drug resistance and survival of breast cancer, which might guide the choice of therapeutic strategies.